Characterization of Mild Steel Case-hardened in Processed Cassava Leaves - D. A. Isadare; M. O. Adeoye; A. R. Adetunji; K. M. Oluwasegun; K. J. Akinluwade; O. S. Adesina (Archives of Current Research International, 2018)
This study characterized 1018 steel case-hardened in processed cassava leaves. The microstructures, phases and case depths of treated samples were characterized and the effect of soaking time on case depth was determined. Standard specimens machined from 1018 steel were pack-cyanided at 950°C using pulverized cassava leaves combined with barium trioxocarbonate IV, BaCO3 energizer. The treated samples were characterized with Advanced Optical Microscope, Scanning Electron Microscope and X-Ray Diffractometer. Results from these tests formed the basis of conclusion. The results showed formation of appreciable cases whose case depths increased with soaking time. The XRD result revealed that the cases contained cementite (Fe3C), silicon carbide (SiC), iron-silicon-carbon (FeSiC) and iron silicide (FeSi) phases which are responsible for surface hardness.